RESPON PERTUMBUHAN JAHE MERAH (Zingiber officinale Rosc.) TERHADAP PEMBERIAN NAUNGAN DAN BEBERAPA TEKNIK BERTANAM - Lili Wahyuni; Asil Barus; Syukri Syukri (Jurnal Agroekoteknologi, 2013)
This study aims to determine the growth response of ginger (Zingiber officinale Rosc.) On the provision ofshade and some farming techniques. Implemented in the district land Labuhan Deli, Deli Serdang regency inOctober 2011 until March 2012. The study uses a separate plot design (RPT) is played with 2 main plotconsisting of shade and without shade. Sub plot consists of 3 level ie beds, baskets and polybag. The resultsshowed that shade significantly affect plant height MAP (Moon after plant) aged 3 and 4 MAP, number oftillers and number of leaves MAP ages 2 and 4, the distance between the tiller and rhizome wet weight / plantage 4 MAP. Farming techniques significantly affect plant height MAP aged 3 and 4, the number of tillers andnumber of leaves aged 2, 3 and 4 MAP, the distance between two MAP tiller, rhizome weight per plant age 4MAP. Interaction of shade treatment and farming techniques significantly affect the number of chicks aged 3and 4 MAP, number of leaves 2 and 3 MAP, and weight per plant ginger rhizome age 4 MAP. But did notsignificantly affect the number of puppies aged 2 MAP, the number of leaf age 4 MAP, distance anatar tiller 2,3 and 4 MAP and MAP age 4 diameter rods.Key words : ginger, shade, planting techniques